2011
DOI: 10.1080/10584609.2011.616875
|View full text |Cite
|
Sign up to set email alerts
|

Representative Communication: Web Site Interactivity and Distributional Path Dependence in the U.S. Congress

Abstract: We examine the speed and extent to which members of the U.S. House of Representatives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…18 For example, in the 2006 cross section, out of the twenty-one regressions of the first column of Table 1, none of the ρ a parameters have a greater than 90 percent chance of exceeding the mean of the prior distribution (0.5), and only three have greater than a 75 percent chance of being greater than the prior mean (only casework form, link to FirstGov, and video), or about what one would expect to observe simply from random variation. These findings regarding local-level dependence reinforce those from other studies that find relatively few district-level observed variables that are predictive of website quality (Adler, Gent, and Overmeyer 1998, 591;Cooper 2004, 352;Druckman, Kifer, and Parkin 2007;Druckman et al 2009, 17;Ferber, Foltz, and Pugliese 2005, 147;Esterling, Lazer, and Neblo 2011). The lack of all dependence at this level further demonstrates the absence of unobserved causal variables measured at the district level.…”
Section: Political Research Quarterly Xx(x)supporting
confidence: 84%
“…18 For example, in the 2006 cross section, out of the twenty-one regressions of the first column of Table 1, none of the ρ a parameters have a greater than 90 percent chance of exceeding the mean of the prior distribution (0.5), and only three have greater than a 75 percent chance of being greater than the prior mean (only casework form, link to FirstGov, and video), or about what one would expect to observe simply from random variation. These findings regarding local-level dependence reinforce those from other studies that find relatively few district-level observed variables that are predictive of website quality (Adler, Gent, and Overmeyer 1998, 591;Cooper 2004, 352;Druckman, Kifer, and Parkin 2007;Druckman et al 2009, 17;Ferber, Foltz, and Pugliese 2005, 147;Esterling, Lazer, and Neblo 2011). The lack of all dependence at this level further demonstrates the absence of unobserved causal variables measured at the district level.…”
Section: Political Research Quarterly Xx(x)supporting
confidence: 84%
“…Thus, whereas new organizations must try activities to see how they are judged, established organizations have accumulated knowledge of successful, legitimate actions through their experiences over time. Esterling, Lazer, and Neblo (2011) find that the offices of established congress-people consult their own, narrow history in making decisions regarding their website design, whereas offices of new congress-people tend to draw at random from a broader distribution of choices observed in the field.…”
Section: The Role Of Legitimacy In Ngo Cooperation and Collective Actionmentioning
confidence: 96%
“…There may also be institutional legacies that impact the style of interaction organizations seek to foster with supporters. In a recent analysis from a new institutionalist perspective, Esterling et al (2011) examined the adoption of interactive features in the websites of newly elected American Congresspeople. They found the Representatives do not appear bound to the features choices made by their immediate predecessors, suggesting a degree of freedom from strict path dependence, and opportunity to take advantage of innovations.…”
Section: Discussionmentioning
confidence: 99%
“…They found the Representatives do not appear bound to the features choices made by their immediate predecessors, suggesting a degree of freedom from strict path dependence, and opportunity to take advantage of innovations. However, few did take full advantage of interactive innovations, and their sites tended to reflect the patterns extant in Congress, a phenomenon the authors call ‘distributional path dependence’ (Esterling et al, 2011). Future research should consider whether a similar phenomenon is taking place among the types of organizations examined here.…”
Section: Discussionmentioning
confidence: 99%